Analysis of the Legitimacy of the Istisnā' Contract from the Perspective of Mu'āmalah Verses and Hadith - Ahmad, Upi Sopiah; Yuslem, Nawir; Zein, Achyar (Civiliza Publishing, 2025)
Contract istisnā’ is one of the form contract transaction Which functioning important in transaction production based order, okay in context jurisprudence classic and practice contemporary Islamic economics. Although no mentioned in a way explicit as contract alone in the Qur'an and hadith, legitimacy contract istisnā ' built through generality arguments transaction as well as mechanism istinbā ṭ the law of the fuqahā’. This article aim for analyze legitimacy contract istisnā' in perspective verses and hadiths transaction with use approach ushul fiqh . Research This is study normative Islamic law with method literature (library research), which is based on verses of the Koran, hadith of the Prophet ﷺ , books of tafsir, hadith, fiqh, as well as literature ushul jurisprudence classic and contemporary. Analysis done through study dalālah word verse, analysis’ god hadith, as well as review difference method istinbā ṭ law between sect jurisprudence. Research results show that legitimacy contract istisnā' can confirmed through generality word verses transaction, like order fulfill contract (QS. al- Mā'idah: 1), permissibility sell buy (QS. al-Baqarah: 275), principle clarity transactions (QS. al-Baqarah: 282), as well as prohibition cheating (QS. al- Mu ṭ affifīn: 1-3), which is reinforced by the hadiths of the Prophet ﷺ about contract greetings and practice booking. Difference view between sect jurisprudence related contract istisnā’ reflect difference approach ushul jurisprudence in understand evidence and reality transaction. In a way overall, research This confirm that contract istisnā ' is contract transaction which legitimate in a way sharia and relevant for implemented in practice contemporary Islamic economics during fulfil principles the basis of sharia and maqā ṣ id al- sharī' ah.